DETERMINASI PERENCANAAN, PENGKOORDINASIAN DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PT. PETEKA KARYA TIRTA BATAM - Reni Angriani; Sri Langgeng Ratnasari (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
Competition among companies in the era of globalization increasingly sharp, so that the human resources required to continually able to develop themselves proactively. Every company, whether in the form of state companies or private companies must have an organization and its organizational structure, where lines of authority evident in the organizational structure. The organizational structure in PT. Peteka Karya Tirta Batam shaped line organization, in which the visible unity of commands or command, the lines of authority and responsibility for running vertically, which means the authority of superiors to subordinates down immediately and responsibility of subordinates to superiors. This study focuses on the determination of planning, coordinating and monitoring the performance of employees of PT. Peteka Karya Tirta Batam is located in Batam because here the center of managerial activities performed. The purpose of this study is first to determine the planning is determined partially on the performance of employees. The second to determine the coordination is determined partially on the performance of employees. Third to know surveillance is determined partially on the performance of employees. To four to determine the planning, coordination and supervision is determined simultaneously on the performance of employees of PT. Peteka Karya Tirta Batam. From hasi research and discussion on the results of a comparative analysis of the value of t arithmetic and t table, it can be concluded that the planning variables have the determination to employees performance. Variable coordination has the determination to employees performance. Variable supervision had a determination to employees performance. The results were obtained F count is 82.31 with Sig 0,000 < Î± 0,05 and the coefficient of determination or R2 of 0.765 or 76.5%. 76.5% means that the performance of the affected research planning, coordination and supervision. While the remaining 23.5% is influenced by other variables that are not the focus of this study. Thus these data show that a significant means There determination of planning, coordination and supervision simultaneously on employee performance.